FORMATION OF STUDENTS’ PEDAGOGICAL OPTIMISM USING THE MATERIALS OF GREGORY SKOVORODA’S CREATIVE HERITAGE - Ворожбіт-Горбатюк, Вікторія; Борисенко, Наталія (New Collegium, 2020)
The urgency of the problem of the formation of students’ pedagogical optimism using the materials of G. Skovoroda's creative heritage is of no doubt. it can be explained by the increasing demands of the society on a young person which living in a stressful environment. The ideas and the conclusions are based on the statement about the interconnection of the study of persons’ inner spiritual world, developed by such enlighteners as i. Kant, G. Skovoroda, V. Solovyov, P. Yurkevich. in the article the authors state that the concept of pedagogical optimism has become widespread thanks to the creativity of the humanist and the teacher V. Sukhomlinsky. it is determined the mission of the modern teacher which is supposed the thoughtful help to a young man in his ability to expect good in his future, to feel the spiritual rising, to distribute the inner resources reasonably. The article focuses on the fact that G. Skovoroda’s views based on the knowledge of Christianity, history and culture of the Ukrainian people. The educator saw the basis of pedagogical optimism in the harmonization of microcosm and macrocosm. The harmony from the point of view of pedagogical optimism is manifested through the realized need of the person for activity, which results in emotional, intuitive, social development and indicates the viability of inner strength. in the context of the problem it is of interest is the conclusion that students’ realizing of G. Skovoroda's imperatives takes place through the analysis of G. Konys'ky's convinctions. G. Konys'ky considered that the sobriety is the basis of optimism. The formation of pedagogical optimism denies the promotion of the moral ideal. instead of it the realizing of a concept of good is proposed. Good is everything, all that is valuable for the person in sobriety are health, heroism, procreation, sensual pleasures, sence of wealth and happiness. However, everything must be in reasonable sizes. According to G. Skovoroda the formation of pedagogical optimism depends on the ability and the experience of a person to realize himself, to learn the inner silent joy through the heartiness, his life plans and intentions, his ability to evaluate the achievements through gratitude.